The provisional OMERACT ultrasonography score for giant cell arteritis. Issue 4 (12th December 2022) - Dejaco, Christian; Ponte, Cristina; Monti, Sara; Rozza, Davide; Scirè, Carlo Alberto; Terslev, Lene; Bruyn, George A W; Boumans, Dennis; Hartung, Wolfgang; Hočevar, Alojzija; Milchert, Marcin; Døhn, Uffe Møller; et al.
Abstract : Objectives: To develop an Outcome Measures in Rheumatology (OMERACT) ultrasonography score for monitoring disease activity in giant cell arteritis (GCA) and evaluate its metric properties. Methods: The OMERACT Instrument Selection Algorithm was followed. Forty-nine members of the OMERACT ultrasonography large vessel vasculitis working group were invited to seven Delphi rounds. An online reliability exercise was conducted using images of bilateral common temporal arteries, parietal and frontal branches as well as axillary arteries from 16 patients with GCA and 7 controls. Sensitivity to change and convergent construct validity were tested using data from a prospective cohort of patients with new GCA in which ultrasound-based intima–media thickness (IMT) measurements were conducted at weeks 1, 3, 6, 12 and 24. Results: Agreement was obtained (92.7%) for the OMERACT GCA Ultrasonography Score (OGUS), calculated as follows: sum of IMT measured in every segment divided by the rounded cut-off values of IMTs in each segment. The resulting value is then divided by the number of segments available. Thirty-five members conducted the reliability exercise, the interrater intraclass correlation coefficient (ICC) for the OGUS was 0.72–0.84 and the median intrareader ICC was 0.91. The prospective cohort consisted of 52 patients. Sensitivity to change between baseline and each follow-up visit up to week 24 yielded standardised mean differences from −1.19 to −2.16, corresponding to large and very large magnitudes of change, respectively. OGUS correlated moderately with erythrocyte sedimentation rate, C reactive protein and Birmingham Vasculitis Activity Score (corrcoeff 0.37–0.48). Conclusion: We developed a provisional OGUS for potential use in clinical trials.